Sold Futures? The Global Availability of Metals and Economic Growth at the Peripheries: Distribution and Regulation in a Degrowth Perspective. Issue 2 (22nd June 2014) - Exner, Andreas; Lauk, Christian; Zittel, Werner
Abstract In recent years, the strategic role certain metals play is seen as central to the geopolitics promulgated by state agents in the North. While a switch to renewable energy and an increase in energy efficiency might be instrumental to reducing dependence on fossil energy, it increases dependence on metals. This paper starts from an analysis of the likely availability of metals in the near future and then proceeds to investigate political concerns raised by considering the geological fundamentals of social development at the peripheries of the capitalist world‐system. The inequality of metal stocks, future metal requirements and the ensuing political challenges are investigated, taking copper as an example. The final section is dedicated to the discussion of regulatory challenges in view of multiple constraints on metal extraction. This section also highlights the preconditions of a socially legitimate transition to a renewable energy system in the coming period of socio‐ecological transformation.